Отдел механики эластомерных конструкций горных машин: история создания и развития - Дырда, В.И. (Геотехническая механика, 2012)
Викладено історію становлення та розвитку відділу механіки еластомірних конструкцій гірничих машин. Сформульовані основні задачі відділу за період його існування, та завдання створеної у м. Дніпродзержинську лабораторії нових технологій переробки сировини і промислових відходів, а також описане впровадження розробок у промисловість. History of becoming and development of department of mechanics of elastomeric constructions of mountain machines is laid out. Formulated basic tasks of department for period of his existence, and tasks of the laboratory of new technologies of processing of raw material and industrial wastes created in Dniprodzerjinsk, and also described introduction of developments in industry.